Gerações travestis: corpo, subjetividade e geracionalidade entre travestis do interior de São Paulo - Miguel, Luiz Henrique (Universidade Federal de São Carlos, 2015)
This research seeks understanding how different transvestite's generations that prostitutes themselves in the countryside of São Paulo built their bodies and subjectivities. I seek to understand the existence of the pressure between this identity project and the creation of two categories, the older and younger, observing the detachment and existent approximation between different generation of transvestites, just like specific valuations of some bodies and behaviors from each one of them. The study realized in Sao Carlos and Ribeirao Preto undertook ethnography at the prostitution areas and the transvestites homes, combined with online contacts through social media like Facebook©. Based on Queer theory, the Brazilian studies about the travestite‟s and the the idea of "generationality" and aging, I seek the creation of particular idea of being young and aging as travestite for the ones that prostitute themselves. Seeing that for this group aging is not only related with the age but with a specific relationship with the body, the job market and the social relationships that develops and keep the environment where they live.
Keywords: Gênero; Travestilidade; Geracionalidade; Envelhecimento; Corpo; Gender; Transvestite; Generation; Aging; Body; CIENCIAS HUMANAS::SOCIOLOGIA